The leadership experience - Daft, Richard L.; Lane, Pat (Cengage Learning, 2015)
Master the critical leadership skills and solid understanding of today's theory needed to become an effective business leader in today's turbulent times with Daft's THE LEADERSHIP EXPERIENCE, 6E. Acclaimed author Richard Daft helps you explore the latest thinking in leadership theory and contemporary practices at work within organizations throughout the world. You will examine emerging topics, including enhancement of emotional intelligence, leadership vision and courage, leadership of virtual teams, and open innovation, and will connect those topics to recent world events such as ethical scandals and political turmoil.